KAJIAN PERBANDINGAN PENGARUH PENGGUNAAN DINDING PRECAST DENGAN DINDING KONVENSIONAL PADA PROYEK CORDOVA SEMARANG - Rohman, Muhamad Arif; Wibowo, M Agung; Nuroji, Nuroji (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
Innovation in the world of construction is something that is indispensable, one of theinnovations in the construction sector is precast. The use of precast is expected to beable to reduce project costs to accelerate the duration of work. But in fact, theproducts of innovation in the world of construction have not been fully able to havea positive impact, both in terms of cost, quality, time, waste, on project development.Products of innovation are usually not necessarily in accordance with the wishesand needs of the customer. The purpose of this research is to analyze thecomparison of products in terms of time, cost, quality, waste, and in terms of K3Lbetween projects using precast walls and projects using the lightweight brick wallmethod. This research was conducted by (1) conducting a project simulation if theproject did not use precast, (2) comparing a real project with a simulation project interms of cost, quality, time, waste, and K3L. The use of precast in the Cordovaproject when compared to a simulation project that uses lightweight bricks results in(1) in terms of time saving 36,84 % on the simulation results project (2) in terms ofcosts can be reduced by Rp. 101.488.543,99 (3) in terms of quality precast materialhas The quality is better than the lightweight bricks (4) in terms of waste, in thesimulation result project it creates more waste (5) in terms of K3L, the use ofprecast is more environmentally friendly than the simulation results project.